Does the European Union need a ‘Drought Directive’? A legal perspective - Jancewicz, Katarzyna Aleksandra (Teisė, 2024)
With global warming progressing, droughts are anticipated to increase in frequency in the European Union. However, under the current EU legal framework, they remain on the margin of water management policies. To adapt to changing natural conditions, the Member States should take a more proactive approach to drought mitigation. The policy options on how to accelerate such a transition encompass the continuation of reliance on soft-law guidances, the amendment of the Water Framework Directive or the adoption of a ‘European Drought Directive’ – a new, up-to-date, all-encompassing legal instrument. This paper analyses those policy options from a legal perspective. It also exposes problems and benefits they can bring if and when pursued. As the Water Framework Directive remains ‘fit for purpose’, the priority shall be given to updating existing soft-law guidances and their translation into all official EU languages. However, there are strong arguments in favour of future legislative reform. This paper submits that a more proactive approach would conform more fully to EU primary law. Nevertheless, irrespective of the chosen policy option, coordination of drought mitigation and measures under existing EU water legislation at the river basin district level must be ensured.